The Burden of Viruses in Pneumonia Associated With Acute Respiratory Failure: An Underappreciated Issue - Shorr, Andrew F; Fisher, Kristen; Micek, Scott T; Kollef, Marin H (Chest, 2018)
Pneumonia associated with mechanical ventilation (MV) results in substantial mortality and represents a leading reason for the use of antibiotics. The role of viruses in this setting is unclear. Identifying a viral cause in such instances could facilitate antibiotic stewardship. We performed a secondary analysis of a prospective cohort with pneumonia requiring MV. We included both cases occurring in the community and hospital-onset cases and classified patients according to the cause of the pneumonia. The prevalence of viral pathogens represented the primary end point. We identified variables independently associated with isolation of a viral organism as the sole pathogen. The cohort included 364 patients, and a virus was the sole pathogen in 79 cases (21.7%). The most common viruses included rhinovirus/enterovirus (n = 20), influenza A (n = 12), and respiratory syncytial virus (n = 11). The rate of in-hospital death was high (37.2%) and did not differ from that seen in other patients (36.5%). The duration of MV, hospital length of stay, and 30-day readmission rates also did not differ based on the cause of pneumonia. Two variables were independently associated with recovery of a virus: an Acute Physiology and Health Evaluation II score of < 26 (adjusted odds ratio [AOR], 0.51; 95% CI, 0.28-0.93; P = .027) and stem cell transplantation (SCT) (AOR, 4.39; 95% CI, 2.03-9.50; P = .001). A sensitivity analysis excluding patients who underwent SCT did not substantially alter our observations. Viruses represent a major cause of pneumonia in critically ill patients requiring MV. Identifying such subjects presents an opportunity for discontinuing antibiotics. Clinicians should consider systematically evaluating patients with pneumonia requiring MV for viral pathogens.